AKTIVISME PETANI TRANSNASIONAL: PERJUANGAN LA VIA CAMPESINA DAN SERIKAT PETANI INDONESIA UNTUK KEDAULATAN PANGAN - Gunawan Lestari Elake; Retno Susilowati; Ferdiansyah R (LPSDI Bina Patria, 2022)
This study aims to understand the transnational peasant activism of La Via Campesina and Serikat Petani Indonesia in striving for food sovereignty agenda, both at the global and national levels. This study uses social movements and transnational activism as theoretical frameworks. The data collection techniques is document analysis. This study shows that the struggle for food sovereignty simultaneously occurs in two model of transnational activism: externalization and internalization. La Via Campesina seeks to internationalize and institutionalize the food sovereignty agenda at the global level, while Serikat Petani Indonesia aims to change public policy at national level